Factors impacting the implementation process of automated construction progress monitoring - Hannan Qureshi, A. (Ain Shams University, 2022)
Automated monitoring technologies are being praised in the construction sector due to effective and efficient outcomes. However, hesitation remains towards its adoption, and one of the reasons is the lack of theoretical understanding towards effective implementation. This study aims to develop a theoretical framework highlighting the factors impacting the effective performance of automated monitoring. Overall, 36 factors were identified under four technological categories. The knowledge framework has been developed with the help of data collected by adopting a structured literature review, questionnaire-based survey, and statistical analysis techniques. The developed technological framework highlights the most impactful factors for each close-range automated monitoring process and technology. This study provides the base conceptual foundation to stakeholders towards the theoretical understanding of automated monitoring processes and technologies for factors that impact the outcomes. Â© 2022